2013
DOI: 10.1002/jbio.201300030
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Raman spectroscopy for detection of oral neoplasia: A pilot clinical study

Abstract: We report a pilot study carried out to evaluate the applicability of in vivo Raman spectroscopy for differential diagnosis of malignant and potentially malignant lesions of human oral cavity in a clinical setting. The study involved 28 healthy volunteers and 171 patients having various lesions of oral cavity. The Raman spectra, measured from multiple sites of normal oral mucosa and of lesions belonging to three histopathological categories, viz. oral squamous cell carcinoma (OSCC), oral submucous fibrosis (OSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 45 publications
1
73
0
Order By: Relevance
“…Previous studies on¯nger-print and high wavenumber region have demonstrated that buccal and labial mucosa, keratinized or masticatory mucosa and specialized mucosa on the tongue can be classi¯ed as distinct clusters of subsites. [34][35][36] While some studies indicate that these subsite-anatomical di®erences confound the healthy and pathological discrimination, 37 other studies have stated that the inherent anatomical di®erences may not hinder healthy vs pathological classi¯cation. 47 In the present study, Raman spectroscopic di®erences between the three common subsites of oral cancer development in the Indian subcontinent-buccal mucosa, movable mucosa of the lip and tongue were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on¯nger-print and high wavenumber region have demonstrated that buccal and labial mucosa, keratinized or masticatory mucosa and specialized mucosa on the tongue can be classi¯ed as distinct clusters of subsites. [34][35][36] While some studies indicate that these subsite-anatomical di®erences confound the healthy and pathological discrimination, 37 other studies have stated that the inherent anatomical di®erences may not hinder healthy vs pathological classi¯cation. 47 In the present study, Raman spectroscopic di®erences between the three common subsites of oral cancer development in the Indian subcontinent-buccal mucosa, movable mucosa of the lip and tongue were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the authors also suggest the use of anatomy-matched algorithms to increase discrimination between healthy and abnormal conditions. 37 There exist ambiguities in the anatomical classi¯cation of the buccal mucosa, tongue and lip subsites. Thus, in the present study, spectral contrast between the anatomical sites buccal mucosa, lip and tongue were investigated¯rst in healthy as well di®erent pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo Raman spectroscopy has shown efficacy in the detection of normal tissue, PMDs, cancer, and even of early changes such as cancer fieldeffects or malignancy-associated changes in the oral cavity (Singh et al 2012;Krishna et al 2014). However, the clinical applications of Raman spectroscopy have been limited by both the difficulty of capturing inherently weak tissue Raman signals and the relatively slow speed of spectrum acquisitions (Guze et al 2009).…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…The essential prerequisites for RS are biochemical changes that happen during neoplastic transformations in tissues [2]. Consequently, pathologic Raman spectra can largely be separated based on protein, DNA, and lipid (phospholipids and fatty acids) related spectral features.…”
Section: Rs Advantagesmentioning
confidence: 99%